Mike Kelley - Meyer-Hermann, Eva; Mark, Lisa Gabrielle; Mike Kelley Foundation for the Arts; Mike Kelley Amsterdam. Stedelijk Museum 2012-12,15; Exhibition Paris. Centre Pompidou 2013-5,2; Exhibition New York. MoMA PS1 2013-10,13; Exhibition Los Angeles. The Museum of Contemporary Art 2014-3,23 (Amsterdam : Stedelijk Museum Amsterdam, 2013)
"From the mid-1970s, Mike Kelley assembled an incredibly diverse and often controversial body of work. A multidisciplinary impresario, he created works on paper, paintings, sculpture, video, installation, and performance art that managed to be at once shocking yet humorous, complex yet accessible. This companion volume to a much-anticipated exhibition brings a fresh understanding to the artist's work by seeking to address the more poetic aspects of Kelley's work through Eva Meyer-Hermann's unique curatorial approach. Here she presents individual works in new combinations that cross the boundaries of chronology, bodies of work, and former artistic project groups. Identifying themes such as architecture, language, identity, Informe, power, modernisms, nostalgia, and religion, the book represents ideas that have informed Kelley's work throughout his career. As a result, the overarching lines of his oeuvre become visible and accessible. This book features essays, a fully annotated plate section, and a newly researched and revised biography and bibliography of Kelley's work. The publication promises to be the definitive work on the artist"--
Live Dead: Mike Kelley's Music / Branden Joseph -- Mike Kelley: Sublevel / George Baker -- Mike Kelley and the Comedic / John C. Welchman -- Interview with Mike Kelley / Eva Meyer-Hermann.
Exhibition December 15, 2012-April 1, 2013
Exhibition May 2-August 5, 2013
Exhibition October 13, 2013-February 2, 2014
Exhibition March 23-July 28, 2014
Includes bibliographical references.
boek
Keywords: Kelley, Mike; ART / Individual Artists / General